Can home visits for early child development be implemented with sufficient coverage and quality at scale? Evidence from the SPRING program in India and Pakistan - Zelee Hill; Shamsa Zafar; Seyi Soremekun; Siham Sikander; Bilal Iqbal Avan; Reetabrata Roy; Sarmad Aziz; Divya Kumar; Nazia Parveen; Shumaila Saleem; Deepali Verma (Frontiers in Nutrition, 2023)
There is limited evidence from low and middle-income settings on the effectiveness of early child development interventions at scale. To bridge this knowledge-gap we implemented the SPRING home visiting program where we tested integrating home visits into an existing government program (Pakistan) and employing a new cadre of intervention workers (India).
Keywords: Child marriage, Girls mental health